COMPOSITION OF CATCH AND FEASIBILITY ANALYSIS OF BOAT CHART AT THE BUNGUS OCEAN FISHERY PORT - Soleha, Siti; Syaifuddin, Syaifuddin; Brown, Arthur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRAKThis research was conducted in September 2021 at the Bungus Ocean Fishing Port, West Sumatra Province. This study aims to determine the type of catch, analyze the technical and financial aspects of the fishing business and determine the feasibility of the fishing gear on the boat lift net. The method used in this research is the survey method. From the results of this study, the main catches (HTU) were squid, scad, mackerel, and anchovies while the by-catch (HTS) were skipjack and tuna. The financial analysis and profitability of the lift-net fishing business shows that the capture fisheries business with this tool is financially profitable and has a short payback period. The analysis of the feasibility of fishing business by fishermen for a full year is feasible to be developed, because the total revenue is greater than the total revenue is greater than the total cost and the value of Revenue Cost Ratio > 1. This can be interpreted that fishermen are classified as profitable. Keyword: Lift net, catch, financial analysis and feasibility